PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR PERTANIAN - Monica Oktavia; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
Research to identify the affect of Corporate Social Responsibility (CSR) to investor response had been done many times, but the results were inconsistent. The objective of this research was to identify the affect of CSR to investor response in the agricultural sector company.The CSR was measured by using indicators of the Global Reporting Index (GRI) and the response of investors was measured by  using the Cumulative Abnormal Return (CAR). Meanwhile this study used Return On Asset (ROA), firm size, Debt to Equity Ratio (DER), and market share as control variables. The samples used in this research  were 60 firm years in the agriculture sector that were listed in Indonesia Stock Exchange in the period of 2008-2012.The results showed that CSR had no significant effect on CAR. As control variables, ROA and market share had significant positive effect on CAR. Firm size no significant negative effect on CAR. While DER no significant positive effect on CAR.